Deskripsi Pemanfaatan Media Pembelajaran Berbasis Visual Dalam Menstimulasi Perkembangan Kognitif Anak Usia Dini - Fitriyani, Rini; Qomariah, Annisa (CV. Multi Kreasi Media, 2026)
This study aims to describe the use of visual-based learning media to stimulate the cognitive development of early childhood. The approach used was descriptive qualitative, with teachers and early childhood children in early childhood education institutions as subjects. Data collection techniques included observation, in-depth interviews, and documentation. The results showed that visual media such as pictures, picture cards, posters, animated videos, and visual aids can improve children's attention span, memory, symbolic thinking skills, and simple problem-solving skills. The use of visual media also helps teachers convey abstract concepts in a more concrete and understandable way for children. Challenges identified include limited resources and varying teacher skills in developing visual media. This study recommends improving teacher competency in developing and utilizing contextual and child-friendly visual media.